Kuantitatif ANALISIS KETERJANGKAUAN DAN POLA SEBARAN SEKOLAH NEGERI BERBASIS INFORMASI GEOGRAFIS (SIG) DI KECAMATAN SAWAN, KABUPATEN BULELENG : KETERJANGKAUAN DAN POLA SEBARAN - Dharma, I Gusti Bagus Wirya; Wisnawa, I Gede Yudi; Budiarta, I Gede (Universitas Pendidikan Ganesha, 2024)
School analysis is very important in improving the quality of education in Sawan sub-district. The school analysis can help in determining school needs, resource allocation and determining sustainable development plans. In addition, the school analysis is also used to identify and describe the condition and service potential of schools in Sawan sub-district. The objective of this study include: Analyze the level of community affordability of public school locattions in Sawan Sub-district, Buleleng Regency based on buffering analysis. Analyze the distribution pattern of public schools in Sawan Sub-district based on Nearsest Neighbor Analysis. The method used is quantitative descriptive method, data analysis includes buffer analysis, nearest neigbor analysis and field survey for data collection of coordinate points. The result of this include: analysis of school outtreach to community settlements using the buffer method, at the primary school level, an area of 56.377 Km² out of a total of 91.303 Km² of residential areas can be reached properly, identifying the reach of primary schools to settlements is evenly distributed and accessibility is very adequate. At the junior high schools level, 11 villages are well served, but 3 villages are not optimally served because the settlements are outside the radius of 1.000 meters from the nearest hunior high school. At the SMA/SMK, most residential areas can be reached, except for 1 village that is not optimally served because is is outside the radius of 3.000 meters from the nearest SMA/SMK. Analysis of the distribution pattern of public schools using the Nearest Neighbor Analysis method at 52 location point indecates a clustered or unevenly distributed pattern, with a value of T I = 0.801924 and z-score =-2,732523.